PET-Recebe: health education in the teaching of parasitology - Doralice Conceição da PAZ NETA; Ingrid da Silva Florêncio FREIRE; Wesllen David Silva VILA; Kamylle Cynnara Tavares da SILVA; Rodrigo Ferreira da SILVA; Igor Marley Pereira de ANDRADE; Caroline Paiva da SILVA; Isabela Marques de LIMA; Nayara dos Santos ARAÚJO; Rutyelle Moreira de Melo SOUSA; Mariana Santana QUEIRES; Yasmin Vitória Moura de SENA; et al. (Elo)
Health education is important for building knowledge and modifying behaviors in the school population, as well as contributing to a humanized and ethical academic formation. The PET-Parasitology Group conducts health education activities for high school and elementary students, aiming to fill gaps in the understanding of parasitology teaching. Through theoretical-practical workshops, students were instructed on the biology of parasites, their infections, transmission, prophylaxis, diagnosis, and treatment. The students reported popular knowledge that was addressed scientifically, revealing understanding of the topic and its preventions. The use of effective tools and teaching laboratory infrastructure are crucial for the success of health education actions, highlighting their importance in parasitology teaching and academic formation.